GENETIC BASES OF HETEROSIS AND ITS CONTRIBUTION TO MODERN AGRICULTURE - de Sousa Júnior, Hamilton Teixeira; Gomes, Matheus da Silva; André Júnior, José; Melo, Carlos Cicinato Vieira; de Araújo, Nicolas Oliveira; Freire, Ana Izabella; de Souza, Filipe Bittencourt Machado; Missasse, Wellington Ferreira; De Souza, Giovanna Maciel (Seven Editora, 2026)
Heterosis, or hybrid vigor, is the phenomenon in which hybrid individuals exhibit superior performance compared to their parents, particularly in traits such as growth, productivity, and physiological vigor. This phenomenon is of great importance in plant breeding and is widely used in crops such as maize and rice, where it significantly contributes to increased agricultural productivity. Studies on heterosis began in the 18th century with hybridization experiments and were later expanded by researchers such as Mendel, Darwin, and Shull, who observed greater vigor in plants derived from crosses compared to those obtained through self-fertilization. From these studies, heterosis began to be applied in the production of hybrid cultivars. Several hypotheses have been proposed to explain the genetic basis of heterosis, with the dominance, overdominance, and epistasis theories standing out, involving different forms of gene interaction. Despite scientific advances, the phenomenon is still not fully understood and remains the subject of studies in molecular genetics and genomics. The measurement of heterosis can be performed using different methods, comparing the performance of the hybrid with that of its parents or with standard cultivars. Its application provides benefits such as higher productivity, plant uniformity, and greater efficiency in genetic improvement. Thus, heterosis represents one of the most important contributions of genetics to agriculture, being essential for the development of more productive cultivars adapted to market demands.